Prediction Supply Modelling for High-Cost Housing in Malaysia - Fazilah Ramli; Rozlin Zainal; Maimunah Ali (International Journal of Supply Chain Management, 2019)
Oversupply and overhang among the high-cost housing type has become a blazing field that is often discussed in the press due to the failure in getting a balance of construction demand and supply unit. The basic purpose of the research is to develop a prediction modelling for high-cost housing supply based on the macroeconomic factors. The investigation involved the improvement of the analytical framework by synthesizing the models and framework advanced by a past analyst on the housing supply market framework. As initial, macroeconomic data of MHPI, GDP, BLR, CPI, population size, PCI, CBI, housing demand rate and housing stock index from 2007 to 2017 are collected from National Property and Information Centre (NAPIC) and Department of Statistics Malaysia (DOSM) website. The prediction of the housing supply is investigated using Multiple Regression Analysis (MRA). Based on these problem, the investigation contended that the housing supply prediction model will be accomplish using experimental data from economic data with supported from macroeconomic factors such as world borrowing cost, outflows of foreign capital, subprime crisis, population characteristics, migration, urbanization, stamp duty exemption, moratorium, RPGT, and also microeconomic factors such as location and accessibility, basic and public facility, financial loan, location and placement, credit facility, construction cost, development approval, price and rental and housing stock.